3D printed anti-icing and de-icing system based on CNT/GNP doped epoxy composites with self-curing and structural health monitoring capabilities. (31st December 2020) - Cortés, A; Sánchez Romate, Xoan F; Jiménez-Suárez, A; Campo, M; Prolongo, M G; Ureña, A; Prolongo, S G
Abstract: The strain-sensing, self-curing and self-heating capabilities of a 3D printed circuit made of a graphene nanoplatelet and carbon nanotube reinforced resin, have been widely explored. These materials exhibit high Joule's heating effect capabilities that can be used for post-curing processes. More specifically, the values of glass transition temperature reached by Joule's heating post-curing were very similar to those obtained by conventional oven heating. The temperature profile along each individual ribbon was relatively homogeneous, being an indicative of a good nanoparticle dispersion, confirmed by field emission gun scanning electron microscope analysis. Furthermore, the proposed printed circuits showed excellent strain-sensing capabilities with a much higher strain sensitivity, with a gauge factor of 6–8, in comparison to conventional metallic gauges or bulk nanocomposites, with a gauge factor of around 2, showing also good linearity. In addition, the breakage of individual ribbons can be easily detected by the strain-sensing system as a sharp increase of the electrical resistance. Finally, temperature compensation tests showed that, in case of printed ribbon breakage, it is possible to keep constant the average temperature of the circuit by raising the applied voltage to avoid ice accretion. Thus, with none to two broken ribbons, the 3D printed circuit can act as an efficient anti-icing and de-icing system.